Odpowiedzi

2010-04-12T21:53:37+02:00
1.
a)2(3x 1) (4x 3) x =5(x 2) 3(x 2) 15
6x – 2 – 4x +3 +x = 5x + 10 -3x +6 – 15
6x-4x+x – 5x + 3x = 10 +6-15+2-3
X=0
b ) 3x/4 - 1+4x/2= 3/8 - x / x 8
6x - 4 + 16x= 3 - x
6x+16x +x=3+4
23x=7/:23
x = 7/ 23

2.
a) 2(3x 5) 2(1x) >3 4(2 x)
6x – 10 + 2 – 2x > 3 – 8 + 4x
6x – 2x – 4x > 3- 8 + 10 – 2
0>3

b) 2x - 3 (x-1)/ 2 ≤ x - 1 / x 2
4x - 3(x-1) ≤ 2x - 2
4x - 3x +3 ≤ 2x - 2
4x - 3x - 2x ≤ - 2 - 3
-x≤-5 / : (-1)
x≥5

7.
cx − y = x +1 / :1
cx-y/1 = x
x= cx-y/1